Tradução, adaptação e validação da escala self-efficacy and their child's level of asthma control : versão brasileira - Gomes, Ana Lúcia Araújo (2016)
GOMES, Ana Lúcia Araújo. Tradução, adaptação e validação da escala self-efficacy and their child's level of asthma control : versão brasileira. 2015. 183 f. Tese (Doutorado em Enfermagem) - Faculdade de Farmácia, Odontologia e Enfermagem, Universidade Federal do Ceará, Fortaleza, 2015. === Submitted by denise santos (denise.santos@ufc.br) on 2016-03-01T13:59:02Z No. of bitstreams: 1 2015_tese_alagomes.pdf: 2092579 bytes, checksum: 40cf288b352910c78d4d3d0615ed3970 (MD5) === Approved for entry into archive by denise santos(denise.santos@ufc.br) on 2016-03-01T14:00:02Z (GMT) No. of bitstreams: 1 2015_tese_alagomes.pdf: 2092579 bytes, checksum: 40cf288b352910c78d4d3d0615ed3970 (MD5) === Made available in DSpace on 2016-03-01T14:00:02Z (GMT). No. of bitstreams: 1 2015_tese_alagomes.pdf: 2092579 bytes, checksum: 40cf288b352910c78d4d3d0615ed3970 (MD5) Previous issue date: 2015 === Efforts to improve the self-efficacy of parental care in the care of childhood asthma can result in control of the disease. The objective was to translate, adapt and validate the Self-Efficacy and Their Child's Level of Asthma Control scale into Portuguese and verify the reliability and validity of the instrument to detect the self-efficacy of parental care in the control of childhood asthma. To perform the evaluation stage of the psychometric properties was made, first the translation and cultural adaptation of Self-Efficacy and Their Child's Level of Asthma Control of asthma control in the Brazilian version from the guidelines Beaton et al. (2007). After the adaptation process, we obtained a range of 17 items with five response options (from strongly disagree to strongly agree). By also dealing with a methodological type of research with a quantitative approach, the scale was submitted to validity and reliability. Seven judges performed the content validity guided Pasqualy (2010), reaching an acceptable CVCT, keeping the total of items and the original scale score (17-85 points). The clarity of language dimensions, relevance practical and theoretical relevance, showed respectively a total CVCT of 0.88, 0.90 and 0.89. Data collection through a home visit was realized from August 2014 to January 2015. A sample of 216 parents who care of children with asthma, regularly monitored in PROAICA one of the three Primary Care Units Fortaleza SER I, said in addition to the scale, a sociodemographic questionnaire and issues related to children's health. Exploratory factor analysis was adequate to evaluate the Brazilian version (Kaiser- Meyer-Olkim- 0.879 and sphericity Bartlett p<0.001) confirmed the existence of two factors (expectation of efficacy and expected results) and suggested withdrawal item 07 of the Brazilian version of the scale. The testing of hypotheses has been proven, as it was found that “parents who care” with less than nine years of schooling, obtained lower scores in self-efficacy in the control of childhood asthma and “parents who care” with higher scores of self-efficacy achieved better asthma control parameters Children. Thus, the validity of the construct by contrasted groups found a statistically significant association between self-efficacy levels and the following variables: age (p=0.019), education (p=0.001); occupation of parents (p=0.015 unscheduled physician visits (p=0.001), visits to emergencies (p=0.000), hospitalization in the last 12 months (p=0.005), limitation of physical activity (p=0.003), absenteeism school (p=0.000), disturbed sleep (p=0.000) and to differentiate the control medication crisis medication (p=0.004), among others. The Cronbach's alpha was 0.87, with 17 items demonstrated high Internal consistency of the instrument, attested by the ICC (p=0.001, CI=95%). with an average of 0.871 Considering the withdrawal of item 07, the Cronbach's alpha with 16 items resulted in a value of 0.92 ., maintaining the scale as a reliable tool Test-retest stability was calculated using the Spearman-Brown coefficient (0.80) and Pearson's correlation coefficient (r=0.65; p=0.001), showing that the correlation the results of the two applications is strongly positive. It was concluded therefore that it obtained a reliable instrument, valid and able to assess the reliability and the expected results of the “parents who care” in the control of childhood asthma instrument. === Esforços para melhorar a autoeficácia de pais/cuidadores no cuidado da asma infantil podem resultar no controle da enfermidade. Objetivou-se traduzir e adaptar a escala Self-Efficacy and Their Child's Level of Asthma Control: versão brasileira e verificar a confiabilidade e a validade do instrumento para detecção da autoeficácia dos pais/cuidadores no controle da asma infantil. Trata-se de uma pesquisa do tipo metodológica com abordagem quantitativa realizada em duas etapas na qual a primeira foi à tradução e adaptação cultural da Self-Efficacy and Their Child's Level of Asthma Control gerando uma versão brasileira com17 itens e cinco opções de respostas e a segunda etapa a avaliação das propriedades psicométricas onde a validade e confiabilidade da escala foram testadas gerando a versão final com 16 itens. Sete juízes realizaram a validade de conteúdo, tendo alcançado um CVCt aceitável, mantendo-se o total de itens e pontuação da escala original (17 a 85 pontos). As dimensões de clareza de linguagem, pertinência prática e relevância teórica, apresentaram respectivamente, um CVCt total de 0,88, 0,90 e 0,89. A coleta de dados através de visita domiciliar foi realizada no período de agosto de 2014 a janeiro de 2015. Uma amostra de 216 pais/cuidadores de crianças com asma, regularmente acompanhada no PROAICA de uma das três Unidades de Atenção Primária de Fortaleza da SER I, respondeu, além da escala, a um questionário sociodemográfico e questões associadas à saúde da criança. A análise fatorial exploratória mostrou-se adequada para avaliação da versão Brasileira (Kaiser- Meyer- Olkim- 0,879 e a esfericidade de Bartlett p<0,001), confirmou a existência de dois fatores (expectativa de eficácia e expectativa de resultados) e sugeriu a retirada do item 07 da versão brasileira da escala. A testagem de hipóteses foi comprovada, pois se constatou que pais/cuidadores, com menos de nove anos de escolaridade, obtiveram menores escores de autoeficácia no controle da asma infantil e pais/cuidadores com escores mais elevados de autoeficácia obtiveram melhores parâmetros de controle da asma das crianças. A validade de construto por grupos contrastados verificou associação estatisticamente significante entre os níveis de autoeficácia e as seguintes variáveis: idade (p=0,019), escolaridade (p=0,001); ocupação dos pais/cuidadores (p=0,015) consultas médicas não programadas (p=0,001), visitas às emergências (p=0,000), hospitalizações nos últimos 12 meses (p=0,005), limitação de atividade física (p=0,003), absenteísmo escolar (p=0,000), sono prejudicado (p=0,000) e saber diferenciar a medicação de crise de medicação de controle (p=0,004), dentre outras. O alfa de Cronbach demonstrou uma alta consistência interna do instrumento, atestada pelo CCIC (p=0,001; IC=95%) com uma média de 0,871. Considerando-se a retirada do item 07, o alfa de Cronbach com os 16 itens resultou em um valor de 0,92, mantendo a escala como um instrumento confiável. A estabilidade teste-reteste foi calculada por meio do coeficiente de Spearman-Brown (0,80) e do coeficiente de Pearson (r=0,65; p=0,001), demonstrando que a correlação entre os resultados das duas aplicações é fortemente positiva. Concluiu-se, portanto que se obteve um instrumento confiável, válido e capaz de avaliar a expectativa de eficácia e expectativa de resultados dos pais/cuidadores no controle da asma infantil.